The influence of mental fatigue on brain activity: Evidence from a systematic review with meta‐analyses. (28th February 2020) - Tran, Yvonne; Craig, Ashley; Craig, Rachel; Chai, Rifai; Nguyen, Hung
Abstract: The occurrence of mental fatigue during tasks like driving a vehicle increases risk of injury or death. Changes in electroencephalographic (EEG) activity associated with mental fatigue has been frequently studied and considered a promising biomarker of mental fatigue. This is despite differences in methodologies and outcomes in prior research. A systematic review with meta‐analyses was conducted to establish the influence of mental fatigue on EEG activity spectral bands, and to determine in which regions fatigue‐related EEG spectral changes are likely to occur. A high‐yield search strategy identified 21 studies meeting inclusion criteria for investigating the change in EEG spectral activity in non‐diseased adults engaged in mentally fatiguing tasks. A medium effect size (using Cohen's g ) of 0.68 (95%CI: 0.24–1.13) was found for increase in overall EEG activity following mental fatigue. Further examination of individual EEG spectral bands and regions using network meta‐analyses indicated large increases in theta ( g = 1.03; 95%CI: 0.79–1.60) and alpha bands ( g = 0.85; 95%CI: 0.47–1.43), with small to moderate changes found in delta and beta bands. Central regions of the scalp showed largest change ( g = 0.80; 95%CI: 0.46–1.21). Sub‐group analyses indicated large increases in theta activity in frontal, central and posterior sites (all g > 1), with moderate changes in alpha activity in central and posterior sites. Findings have implications for fatigue monitoring and countermeasures with support for change in theta activity in frontal, central and posterior sites as a robust biomarker of mental fatigue and change in alpha wave activity considered a second line biomarker to account for individual variability. Abstract : There is significant risk of injury during tasks such as driving or operating machinery when mentally fatigued. Reliable biomarkers are needed that warn a fatigued person so they can take preventive action. This review uses meta‐analytic methods to synthesise the results from 21 studies. Results highlight the spectral bands and regions most promising for an EEG biomarker.